Implementation of DC voltage controllers on enhancing the stability of multi-terminal DC grids - Moussa Belgacem; Mohamed Khatir; Mohammed Abdeldjalil Djehaf; Sid Ahmed Zidi; Riyadh Bouddou (Institute of Advanced Engineering and Science, 2021)
Because of the increasing penetration of intermittent green energy resources like offshore wind farms, solar photovoltaic, the multi-terminal DC grid using VSC technology is considered a promising solution for interconnecting these future energies. To improve the stability of the multi-terminal direct current (MTDC) network, DC voltage control strategies based on voltage margin and voltage droop technique have been developed and investigated in this article. These two control strategies are implemented in the proposed model, a ±400 kV meshed multi-terminal MTDC network based on VSC technology with four terminals during the outage converter. The simulation results include the comparison and analysis of both techniques under the outage converter equipped with constant DC voltage control, then the outage converter equipped with constant active power control. The simulation results confirm that the DC voltage droop technique has a better dynamic performance of power sharing and DC voltage regulation.